2010
DOI: 10.1016/j.neubiorev.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Kicking the habit: The neural basis of ingrained behaviors in cocaine addiction

Abstract: Cocaine addiction is a complex and multifaceted process encompassing a number of forms of behavioral plasticity. The process of acquiring and consuming drugs can be sufficiently risky and complicated that the casual drug user may choose not to act on every motivation to use drugs. The repetition of drug seeking and taking, however, often results in the gradual development of drug craving and compulsive drug seeking associated with addiction. Moreover, the complex sets of behaviors associated with drug addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 123 publications
1
91
0
Order By: Relevance
“…On the basis of the pioneering studies by Di Chiara and colleagues in the 1980s that showed that different drugs abused by humans all increase dopamine release within the nucleus accumbens (Di Chiara and Imperato, 1988), numerous pharmacological and molecular studies have substantiated the involvement of the ventral striatum in self-administration of different classes of abused drugs (Ikemoto and Wise, 2004;Pierce and Kumaresan, 2006). More recently, habit-based theories of addiction (Tiffany, 1990;Everitt et al, 1999;Everitt and Robbins, 2005;Pierce and Vanderschuren, 2010) have inspired work on the role of the dorsal striatum in drug use and addiction.…”
Section: Neurobiological Mechanisms Of Compulsive Drug Use Ventral Anmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the pioneering studies by Di Chiara and colleagues in the 1980s that showed that different drugs abused by humans all increase dopamine release within the nucleus accumbens (Di Chiara and Imperato, 1988), numerous pharmacological and molecular studies have substantiated the involvement of the ventral striatum in self-administration of different classes of abused drugs (Ikemoto and Wise, 2004;Pierce and Kumaresan, 2006). More recently, habit-based theories of addiction (Tiffany, 1990;Everitt et al, 1999;Everitt and Robbins, 2005;Pierce and Vanderschuren, 2010) have inspired work on the role of the dorsal striatum in drug use and addiction.…”
Section: Neurobiological Mechanisms Of Compulsive Drug Use Ventral Anmentioning
confidence: 99%
“…How the deficit in NMDA-receptor-dependent long-term depression in the nucleus accumbens core contributes to the behavioral signs of addiction remains to be demonstrated. Studies focusing on the role of cocaine-associated stimuli in drug seeking and taking have indicated that the nucleus accumbens core might provide a gateway by which dorsal striatal mechanisms gain control over behavior, perhaps associated with habitual forms of drug seeking and taking (Everitt and Robbins, 2005;Pierce and Vanderschuren, 2010). These findings are buttressed by converging lines of evidence.…”
Section: Cocainementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it has been shown that the neural response to a methylphenidate challenge differs between cocaine addicts and control subjects [145]. Since the development of addictive behavior relies on concerted neural changes in the VTA, the striatum, the amygdala, and the PFC [44,146], these circuits should be investigated accordingly.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The dorsomedial striatum (DMS), which receives input primarily from the prefrontal cortex [3] , appears to be preferentially involved in the rapid acquisition of actionoutcome behavior [4,5] and is thought to contribute to the early performance of drug-seeking behavior. By contrast, the lateral striatum, which receives input from the sensorimotor cortex [3] , is critical for the acquisition of stimulus-response habitual behavior [4,6] and is thought to be involved in cue-controlled forms of addictive behavior after extensive drug-taking experience [7,8] . The lateral striatum is also involved in the reinstatement of drug seeking after protracted withdrawal and in relapse to a drug-seeking state [9,10] .…”
Section: Introductionmentioning
confidence: 99%